Adoption and use of digital marketing applications among Costa Rican exporting SMEs: a qualitative analysis - Martínez-Villavicencio, José (2021)
Business dynamics have changed in the last decade mostly driven by the technological revolution, and this is especially evident in the strategic approach adopted by organizations to interact with their customers. Seeking to better grasp how SMEs assimilate new digital technologies, this study aims to identify the perceptions on digital marketing among Costa Rican exporting SMEs. The study employs a qualitative approach based on in-depth interviews with directors of SMEs operating in different geographies, business lines, and with different export performance levels (low, medium, and high). By using ATLAS ti8 software to codify and analyze the data, the main findings reveal that exporting SMEs have limited knowledge about the dynamics of digital marketing, and that they lack specialized human capital capable of designing and implementing specific digital marketing strategies. Additionally, the results indicate that exporting SMEs mostly use basic elements of digital tools, even if they consider these digital tools instrumental for creating and sustaining economically meaningful relationships with their customers.